2019
DOI: 10.1159/000499141
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Well-Being and Their Implications for Health Care

Abstract: The paper explains how subjective well-being can be measured, how the resulting data are being used to document human progress and how health care can be changed to take advantage of what has been learned. The evaluations that people make of their own lives document, and permit the explanation of, life satisfaction levels that differ greatly among countries and communities. Research seeking to explain these happiness differences, and their related differences in mortality and morbidity, exposes the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We selected variables pertaining to the following groups: (1) depressive symptoms and characteristics of periods of depression; (2) anxiety symptoms and characteristics of periods of anxiety; (3) neuroticism-related personality traits; (4) physical diseases and lifestyle; (5) PRSs of psychiatric disorders [MDD, schizophrenia, bipolar disorder, attention-deficit hyperactivity disorder (ADHD), alcohol dependence, anxiety disorders] and neuroticism. These were selected because they represent domains or genetic factors previously associated with the course, functional impact or treatment outcomes of MDD and/or wellbeing in the general population (Bartova et al, 2019; Cho et al, 2019; Christensen et al, 2020; Fabbri et al, 2021; Fanelli et al, 2021; Helliwell, 2019; McIntyre et al, 2013; Pain et al, in press; Santini et al, 2020; Spittlehouse et al, 2014; Stranges et al, 2014). For the selection of PRSs to include in the study, we also considered the availability of summary statistics from genome-wide association studies without sample overlap with UKB, to avoid overfitting (Choi, Mak, & O'Reilly, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected variables pertaining to the following groups: (1) depressive symptoms and characteristics of periods of depression; (2) anxiety symptoms and characteristics of periods of anxiety; (3) neuroticism-related personality traits; (4) physical diseases and lifestyle; (5) PRSs of psychiatric disorders [MDD, schizophrenia, bipolar disorder, attention-deficit hyperactivity disorder (ADHD), alcohol dependence, anxiety disorders] and neuroticism. These were selected because they represent domains or genetic factors previously associated with the course, functional impact or treatment outcomes of MDD and/or wellbeing in the general population (Bartova et al, 2019; Cho et al, 2019; Christensen et al, 2020; Fabbri et al, 2021; Fanelli et al, 2021; Helliwell, 2019; McIntyre et al, 2013; Pain et al, in press; Santini et al, 2020; Spittlehouse et al, 2014; Stranges et al, 2014). For the selection of PRSs to include in the study, we also considered the availability of summary statistics from genome-wide association studies without sample overlap with UKB, to avoid overfitting (Choi, Mak, & O'Reilly, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In studies conducted in the general population, the most common way to measure wellbeing is through life evaluations, using life satisfaction questions and questions asking how happy people are with their lives (Helliwell, 2019). These studies have identified a number of variables associated with wellbeing, in particular social support, personality characteristics, chronic diseases such as psychiatric disorders and obesity, lifestyle and socioeconomic status (Helliwell, 2019; Santini et al, 2020; Spittlehouse, Vierck, Pearson, & Joyce, 2014; Stranges, Samaraweera, Taggart, Kandala, & Stewart-Brown, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study in a small number of patients found a social prescribing intervention to be associated with improvements to self-esteem; however, in terms of general practice workload and polypharmacy prescribing, no improvements were attributable (20). Whilst wellbeing is being recognised as an important component and predictor of overall health (21), it is also important to establish whether such interventions may be associated with alleviations to clinical markers such as anxiety and depression. The present study was designed to establish whether participation in an eight-week AoP intervention was associated with changes to levels of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%